2004
DOI: 10.1128/iai.72.5.2827-2836.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileToxin A Carboxyl-Terminus Peptide Lacking ADP-Ribosyltransferase Activity Acts as a Mucosal Adjuvant

Abstract: The receptor binding domains of the most potent mucosal adjuvants, bacterial toxins and plant lectins, are organized in repeat units to recognize specific sugar residues. The lectin-like structure of the C-terminal region of Clostridium difficile toxin A prompted us to investigate the mucosal adjuvant properties of a nontoxigenic peptide corresponding to amino acids 2394 to 2706 (TxA C314 ). We compared TxA C314 adjuvant activity to those of cholera toxin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…Mice that were transcutaneously immunized with CT and CDA developed more prominent anti-CT IgA responses in serum and stool than mice that were transcutaneously immunized with CT alone. These observations and our detection of anti-C. difficile toxin A responses following TCI with CDA alone may reflect immunoadjuvantative properties of the carboxyl terminus of C. difficile toxin A itself (7).…”
Section: Discussionmentioning
confidence: 74%
“…Mice that were transcutaneously immunized with CT and CDA developed more prominent anti-CT IgA responses in serum and stool than mice that were transcutaneously immunized with CT alone. These observations and our detection of anti-C. difficile toxin A responses following TCI with CDA alone may reflect immunoadjuvantative properties of the carboxyl terminus of C. difficile toxin A itself (7).…”
Section: Discussionmentioning
confidence: 74%
“…Because of the insufficient cross-protection elicited by the individual antitoxins, we sought to generate a single immunogen capable of inducing potent neutralizing antibodies against both toxins. The RBD is the immunodominant toxin region of TcdA and possesses potent adjuvant activity due to its lectin-like structural repeats (6,57). In contrast, the neutralizing epitopes in TcdB are primarily confined to the N terminus since preincubation of polysera from aTcdB-immunized mice with recombinant TcdB-RBD did not significantly reduce the serum neutralizing activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrate-binding assays indicated that the rARU of TcdA can preferentially recognize 3ЈHSO 3 -containing oligosaccharides of diverse structures. The biological activation of endothelial cells by the TcdA CRD on endothelial cells and the subsequent induction of leukocyte chemotaxis might also be the underlying mechanism that partially accounts for the potential adjuvant effect of this repeat peptide in vivo (4,31). This TcdA CRD, as the modulin, might also play a key role in the inflammatory response by which the toxin causes tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike for other repeats, little is known about the biological functions of CROPs. Besides carbohydrate-binding activity, the TcdA CRD has an immune modulating effect when used as an adjuvant or carrier protein for mucosal immunization (4,31). Nevertheless, conflicting results have been ob-tained from in vitro studies of the biological activity of the CRD of TcdA alone in different cell culture systems: activation signals were detected in epithelial cells (33), but no activation was observed for monocytes (16).…”
mentioning
confidence: 99%